9(5+x)-6(x+3)=

Simple and best practice solution for 9(5+x)-6(x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(5+x)-6(x+3)= equation:


Simplifying
9(5 + x) + -6(x + 3) = 0
(5 * 9 + x * 9) + -6(x + 3) = 0
(45 + 9x) + -6(x + 3) = 0

Reorder the terms:
45 + 9x + -6(3 + x) = 0
45 + 9x + (3 * -6 + x * -6) = 0
45 + 9x + (-18 + -6x) = 0

Reorder the terms:
45 + -18 + 9x + -6x = 0

Combine like terms: 45 + -18 = 27
27 + 9x + -6x = 0

Combine like terms: 9x + -6x = 3x
27 + 3x = 0

Solving
27 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 3x = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 3x = 0 + -27
3x = 0 + -27

Combine like terms: 0 + -27 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| 14Xy= | | 12=g-15 | | 75=-12 | | (-3-x)(-x+3)= | | 0.2(0.5x-4)7.4=-96 | | x+1/2x-3/2x=1/6 | | v-9=-5 | | 2k^2+3k^2-7k^2= | | -4+5y=-34 | | 3.2(2x+2.1)-0.8=-1 | | y^3+2y^2=36y+32 | | 6b+6=8 | | 15=y-23 | | 6+4X+6X=126 | | -(c+d)-4d+5c-d=0 | | 3b+12+8=-3 | | (3a+b)(2a+b)= | | 2c+3c=109225 | | 2x+3y+4x+5y=0 | | 19g-4h+4-20(g-1)=0 | | x-.7=9.09 | | n+2n+4= | | 7y-27=-32+2y | | 9(k-4)=12 | | 58=-y+179 | | -11x+4+8x-4+3x=0 | | -3x-21=-81 | | -11x+4+8x-4+3x=o | | 5g+7g-4= | | 35x-7y=491 | | 2x+54=2(x+28) | | 4(2x+3)+8=2(X+3)+4 |

Equations solver categories